Heavy Metal Stress Alleviation Through Omics Analysis of Soil and Plant Microbiome - Phurailatpam, Laccy; Dalal, Vijay Kumar; Singh, Namrata; Mishra, Sushma (Frontiers in Sustainable Food Systems, 2022)
Heavy metal (HM) contamination of soil and water resources is a global concern, which not only limits crop yield and quality, but also has serious environmental effects. Due to the non-biodegradable nature and toxicity, high concentration of HMs in food and environment is a serious threat to the entire ecosystem. Moreover, the target of supplying safe and quality food to the rising human population (expected to reach ~9–10 bn by the year 2050), necessitates effective treatment of the HM-contaminated soil. Various microbe-mediated bioremediation strategies such as biosorption, bioprecipiation, biostimulation, etc., have been found to be effective in uptake and conversion of HMs to less toxic forms. Further, in the past few years, the use of soil and plant-associated microbiome for HM stress alleviation is gaining attention among the scientific community. In general, microbes are spectacular in being dynamic and more responsive to environmental conditions in comparison to their host plants. Moreover, with the advancements in high throughput sequencing technologies, the focus is eventually shifting from just structural characterization to functional insights into the microbiome. The microbes inhabiting the HM-contaminated environments or associated with HM-tolerant plants are a source for exploring HM-tolerant microbial communities, which could be used for enhancing bioremediation efficiency and conferring HM tolerance in plants. This review discusses the application of omics techniques including metagenomics, metatranscriptomics, metaproteomics, and metabolomics, for rapid and robust identification of HM-tolerant microbial communities, mining novel HM resistance genes, and fabricating the HM resistome.